Survei Sarana dan Prasarana Pendukung Teknologi di Sekolah Dasar Negeri di Kecamatan Sukadana - Gunawan, Ari; Richiardo, Ricky; Rahmad; Arifahmi Hamzah, Doddy; Porja Daryanto, Zusyah (Universitas PGRI Pontianak, 2024)
The purpose of this study is to determine the ideal standard of technology-supporting facilities and infrastructure in State Elementary Schools throughout Sukadana District, Kayong Utara Regency. The method used in this research is a descriptive selection method with a survey form. The techniques used to collect data in this study are direct observation, direct communication, and documentary study, while the tools used to collect data are observation sheets, interview sheets, and documentation. The population in this study uses saturated sampling. The data analysis technique in this study uses frequency distribution. The results of the study concluded that the technology-supporting facilities and infrastructure in State Elementary Schools throughout Sukadana District, Kayong Utara Regency have not met the ideal standard criteria based on the Minister of National Education Regulation Number 24 of 2007. The availability of facilities and infrastructure in State Elementary Schools throughout Sukadana District, Kayong Utara Regency in 2024 provides an average of 53% of the ideal standard. The ownership of facilities and infrastructure in State Elementary Schools throughout Sukadana District belongs to the schools. The feasibility of facilities and infrastructure in State Elementary Schools throughout Sukadana District, Kayong Utara Regency is categorized as Inadequate.